2010
DOI: 10.1111/j.1742-481x.2010.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐stage Matriderm® and skin grafting as an alternative reconstruction in high‐voltage injuries

Abstract: This article presents a retrospective analysis of a series of nine patients requiring reconstruction of exposed bone, tendons or joint capsules as a result of acute high-voltage injuries in a single burn centre. As an alternative to free tissue transfer, the dermal substitute Matriderm(®) was used in a one-stage procedure in combination with split-thickness skin grafts (STSG) for reconstruction. Nine patients, in the period between 2005 and 2009 with extensive high-voltage injuries to one or more extremities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Matriderm is a highly porous dermal substitute, which consists of a collagen matrix cross-linked to an elastin hydrolysate. It may be employed in a single-stage procedure with immediate STSG [15,16]. One animal study reported that Matriderm showed a better rate of integration compared to other dermal substitutes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Matriderm is a highly porous dermal substitute, which consists of a collagen matrix cross-linked to an elastin hydrolysate. It may be employed in a single-stage procedure with immediate STSG [15,16]. One animal study reported that Matriderm showed a better rate of integration compared to other dermal substitutes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thicker composite grafts have displayed less contracture formation, ultimately with an optimum cosmetic and functional outcome. Some dermal substitutes (e.g., , 1-mm -thick Matriderm ® , a bovine-based collagen I, III, and V and elastin hydrolysate dermal substitute) have also resulted in good clinical outcomes with a one-stage procedure (Haslik et al, 2007;Ryssel et al, 2008;Ryssel et al, 2010). Recently, a single-layer product, Integra ® (IDRT-SL ® ), was introduced for one-stage closure of deep facial surgical wounds in elderly multimorbid patients; studies have shown promising graft-take rates and good functional and cosmetic outcomes (Koenen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…24 However, its thickness is thin, only 1 mm; thus, it should be covered with split thickness skin grafts, causing morbidity of the donor site. [25][26][27][28][29] Furthermore, there are risks of allergic reaction and infection caused by bovine collagen. To overcome these challenges, alternative artificial scaffolds based on poly(ethylene glycol), poly(lactic acid), polycaprolactone, polyphosphates, ceramics and metals have been developed.…”
Section: Discussionmentioning
confidence: 99%